Increasing incidence of cancer of the corpus uteri in the elderly in Canada? Analysis of descriptive data, hysterectomy adjustment and chart review. - Findlater, Andrew Ross. (University of Ottawa (Canada), 1995)
Incidence of cancer of the corpus uteri (of which 89% is endometrial adenocarcinoma) in Canada is declining in women under 70 years of age; in women 70 and over incidence increased from 1969 until 1982 since when it has been stable. These incidence data use as a denominator all women in the population, rather than just women with intact uteri, who constitute the real population at risk. A descriptive analysis was done using data from national databases on incidence, mortality, morphology, method of diagnosis, surgical procedures and population numbers, focussing on incidence in women $\ge$70 years of age. A variety of models for the hysterectomy adjustment all resulted in a trend of increasing incidence in women over 70 years of age; this effect is most important in the most recent period, where the adjustment changes stable crude rates into increasing adjusted ones. Decreasing proportions of diagnosis by death certificate only, and decreasing mortality/incidence ratios in recent periods suggest some improvement in diagnosis in elderly women. Incidence of cancer of the corpus uteri, adjusted for hysterectomy prevalence, is increasing in women over 70 years of age in Canada. There is a cohort effect which may represent residual increased risk from unopposed estrogen use in the 1970s. There is also some (weak) evidence to suggest improved diagnosis of this cancer in elderly women in recent periods. Absolute numbers of cases in women $\ge$70 years are definitely increasing as the population ages. (Abstract shortened by UMI.)
Keywords: Health Sciences, Obstetrics and Gynecology.